Depth diversity profile of polychaete worms in Bahía Chatham, Isla del Coco National Park, Costa Rican Pacific - Sibaja-Cordero, Jeffrey A.; Cortés, Jorge; Dean, Harlan K. (Revista de Biología Tropical, 2012)
The subtidal benthos of tropical islands has been poorly studied in the Eastern Tropical Pacific. Several studies have been published on taxonomic collections from oceanic islands in the region, but ecological features and community structure are practically unknown. In the present study, composition of the polychaete community along a depth gradient from the sand bottom of Bahía Chatham, Isla del Coco National Park, Costa Rica is analyzed. Fifty species of polychaetes belonging to 28 families were found. There is a peak in diversity, abundance and richness at 28-30m. The lowest values occurred at 50m depth with values increasing below this depth. The composition of species changed with depth with some species being found only at depths either less than or greater than 50m. This pattern can be explained in part by the location of the thermocline that occurred at around 50m depth. Citation: Sibaja-Cordero, J.A., J. Cortés & H.K. Dean. 2012. Depth diversity profile of polychates worms in Bahía Chatham, Isla del Coco National Park, Pacific of Costa Rica. Rev. Biol. Trop. 60 (Suppl. 3): 293-301. Epub 2012 Dec 01.